2016
DOI: 10.1111/gbi.12213
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular amorphous carbonates uncover a new biomineralization process in eukaryotes

Abstract: Until now, descriptions of intracellular biomineralization of amorphous inclusions involving alkaline-earth metal (AEM) carbonates other than calcium have been confined exclusively to cyanobacteria (Couradeau et al., 2012). Here, we report the first evidence of the presence of intracellular amorphous granules of AEM carbonates (calcium, strontium, and barium) in unicellular eukaryotes. These inclusions, which we have named micropearls, show concentric and oscillatory zoning on a nanometric scale. They are wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 43 publications
(73 reference statements)
8
60
0
Order By: Relevance
“…It should be mentioned that the carbonates in the phytoplankton are amorphous [1] whereas the studies cited concern well-crystallized carbonates. Values of distribution coefficients in amorphous carbonates (as is the case for thermodynamic data) are quasi non-existent in the literature but it has been shown that amorphous calcium carbonate is a precursor of crystalline carbonate and that a continuum exists between these two stages [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the carbonates in the phytoplankton are amorphous [1] whereas the studies cited concern well-crystallized carbonates. Values of distribution coefficients in amorphous carbonates (as is the case for thermodynamic data) are quasi non-existent in the literature but it has been shown that amorphous calcium carbonate is a precursor of crystalline carbonate and that a continuum exists between these two stages [19].…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular inclusions of amorphous Ba-and Sr-rich calcium carbonates -referred to as "micropearls"have recently been detected in Lake Geneva [1]. Initially, they were thought to exist as agglomerates inside an organic matrix but it was subsequently discovered that they are in fact intracellular mineral inclusions in unicellular phytoplankters.…”
Section: Introductionmentioning
confidence: 99%
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017). The transformation from ACC to crystalline carbonate mineral is commonly suggested to be assoc...…”
Section: Tablementioning
confidence: 99%
“…In recent years, further cases of intracellular precipitation have been documented including amorphous Ca-Mg-Sr-Ba carbonate spheroids in cyanobacteria within a biofilm in the highly alkaline Lake Alchichica, Mexico (Couradeau et al, 2012;Benzerara et al, 2014;Li et al, 2016). Similar Ca-Ba carbonate spheroids (with some Sr), also referred to as 'micropearls', are forming within unicellular eukaryotic phytoplankton within the waters of Lake Geneva (Jaquet et al, 2013;Martignier et al, 2017). Different organisms appear to produce spheroids of different composition (Ca-rich, Ba-rich and Sr-rich), apparently somehow pre-concentrating particular elements which are in low abundance in the ambient water itself.…”
Section: Microspheresmentioning
confidence: 99%
“…Although the composition of those within the Mesaieed mat appears to be that of an amorphous compound, it is likely that this would eventually evolve into a carbonate mineral. The reasons why these bacteria and algae produce intracellular mineral precipitates are unknown, but it is clearly an intracellular biologically controlled process (Benzerara et al, 2014;Cam et al, 2015;Martignier et al, 2017).…”
Section: Microspheresmentioning
confidence: 99%